A virtual rural medicine self learning module for preclerkship students - DeBiasio, Celina; Su, Charles; Campbell, Craig; Wood, Timothy J (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Implication StatementAll Ontario medical schools have a mandatory preclerkship rural placement. Despite these mandatory placements, there is a lack of Canadian rural medicine pre-departure training for students.  We describe a virtual self-learning module (SLM) aimed to enhance medical students’ abilities to provide compassionate care during their rural medicine placements. This SLM improves students’ knowledge about rural health issues while also encouraging exploration of rural career options. Better preparation for a rural medicine placement may lead to an improved experience and eventually an increase in the number of students pursuing rural medicine careers.